2013
DOI: 10.2337/dc12-1780
|View full text |Cite
|
Sign up to set email alerts
|

Glycation Gap Is Associated With Macroproteinuria but Not With Other Complications in Patients With Type 2 Diabetes

Abstract: OBJECTIVEWe investigated whether glycation gap (G-Gap), an index of intracellular glycation of proteins, was associated with diabetes complications.RESEARCH DESIGN AND METHODSWe measured concomitantly HbA1c and fructosamine in 925 patients with type 2 diabetes to calculate the G-Gap, defined as the difference between measured HbA1c, and fructosamine-based predicted HbA1c. Patients were explored for retinopathy, nephropathy, peripheral neuropathy, cardiac autonomic neuropathy (n = 512), and silent myocardial is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…GG, indicating the discordance between HbA 1c and other measures of glycaemic control ( e . g ., GA and fructosamine), has been associated with renal impairment and diabetic nephropathy 19 , 53 55 . GG was shown previously to be a heritable trait 56 , 57 .…”
Section: Discussionmentioning
confidence: 99%
“…GG, indicating the discordance between HbA 1c and other measures of glycaemic control ( e . g ., GA and fructosamine), has been associated with renal impairment and diabetic nephropathy 19 , 53 55 . GG was shown previously to be a heritable trait 56 , 57 .…”
Section: Discussionmentioning
confidence: 99%
“…The glycation gap developed by Cohen et al ( 5 ) is calculated in exactly the same way as HGI except fructosamine replaces directly measured glucose for obtaining a predicted HbA 1c . Several studies have shown that patients with type 2 diabetes with a high glycation gap have greater risk for microvascular or macrovascular complications ( 5 , 10 , 13 , 14 ). HGI and the glycation gap are strongly positively correlated, which suggests they reflect the same biological phenomenon ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study of 503 HD patients reported significant associations between higher fructosamine levels and poorer clinical outcomes and increased mortality [21]. In addition, the glycosylation gap, calculated from the difference between measured HbA1c and fructosamine-based predicted HbA1c, showed a positive association with nephropathy and macroproteinuria in a study of 925 patients with diabetes [22]. The glycosylation gap may be a useful indicator of the severity of complications relating to diabetes.…”
Section: Discussionmentioning
confidence: 99%